Analisis Perbandingan Perhitungan Dana Zakat Menurut Accounting and Auditing Organization for Islamic Financial Institutions (AAO-IFI) dengan Standarisasi Kebijakan Pada Bank Muamalat - B41108120, Purwoko (Jurnal KIAFE, 2014)
Zakat is one of the liability owned by the moslem for the poors, by means to fulfill moslem’s liability to Allah S.W.T. As we know there are several type of Zakat, which is personal zakat and concept of corporate zakat which has to be paid as one of liability to Allah S.W.T and to the humans who receive the zakat (the poors). Based on that case, writer tried to do a research about accounting implemetation for zakat which is practiced by Bank Muamalat. The problem questioned by this research is about how to calculate methods of the zakat funds and compared with two methods stated by Accounting and Auditing Organizations for Islamic Financial Institutions (AAO-IFI) and standardization of Bank Muamalat itself. The goal of this research is to know the methods of calculating the statement of zakat funds in Bank Muamalat and compare it with the calculating methods stated by AAO-IFI. Methods used in this research is a descriptive methods, through case learning which is supported by data collecting through observation, interview dan documentation study. And data used in this research is a secondary data of Bank Muamalat Statement of Financial Position, period 2010 – 2011. The result in this research and analysis for the comparation of Zakat through standarization from Bank Muamalat, shown that Bank Muamalat does this calculation in the net income approach methods, and compared with Accounting and Auditing Organizations for Islamic Financial Institutions (AAO-IFI) that in this calculation, Bank Muamalat didn’t consider the zakat in asset which should be paid, and also the liability included in the shrinkage of aseet in zakat’s, so the payment of zakat could be optimal and appropiated as zakat’s principal in islamic syariat. Keyword: Zakat, Bank Muamalat, AAO-IFI, Comparation